MAMMALIAN SPERMATOGONIAL CELLS - Gonzales Molfino, Hugo Mauricio (2017)
In recent years, the scientifi c community is becoming increasingly interested in the knowledge of the biology of spermatogonia. Th is mini-review aims to announce the progress made in the origin and migration of primordial germ cells, their propagation and renewal, in vitro culture methods as well as the perspectives of the use of spermatogonial stem cells (SSCs) of mammals, mainly in regenerative biology. Mammalian spermatogonial stem cells are a population of cells that are found in very small amounts at the periphery of the seminiferous tubules, from which spermatozoa are produced continuously, throughout the life of the males. Th e SSCs, are the unique adult stem cells that, at this biological complexity level, can be recognized it which allows to deepen investigations about its organization and functions in biological models, diff erent from the most studied mouse, such as humans, cattle, canines, for the importance of its knowledge in the use of strategies in reproductive biotechnology and in regenerative biology.